Validity and reliability of the Indonesian version of Expanded Nursing Stress Scale (ENSS) as a job-stress assessment tool for nurses - Harsono, Hasto; Herqutanto, Herqutanto; Wibowo, Suryo; Kekalih, Aria; Sulistomo, Astrid (UI Scholars Hub, 2024)
ABSTRACT Background: Job stress is a serious health problem in the 21st century because of its high incidence and impact. Nurses are known as a profession that has high risks of stress, has distinctive characteristics, and hence requires a work stress assessment instrument that suits its peculiarities. The Expanded Nursing Stress Scale (ENSS) is a nurse-specific stress assessment instrument that has high validity and reliability (Cronbach's alpha = 0.96) and is widely used in many countries but is not yet available in Indonesian. This study aims to obtain the Indonesian version of ENSS and evaluate its reliability and validity. Method: We applied the 10 steps of ISPOR's (International Society for Pharmacoeconomics and Outcomes Research) transcultural adaptation method, followed by validity and reliability tests on 104 nurses at a private hospital in Jakarta. Result: The Indonesian version of the ENSS questionnaire, consisting of 57 items, was obtained. All of the items were valid, with r values ranging from 0.362 to 0.793. Cronbach's alpha was 0.956, and the reliability test value using test-retest was 0.939. Conclusion: The Indonesian version of the ENSS has proven to be valid and reliable and has excellent internal consistency. The instrument can be used to assess job stress among Indonesian nurses. Keywords: ENSS; Indonesian; work stress; nurse